Peran Pendidikan Aqidah Akhlak dalam Membentuk Siswa Unggul - Padli, Padli; M Darlis, Andi (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
The aim of this research is to find out the Role of Aqidah Akhlak Education in Forming Excellent Students. The type of this research is library research and with the approach to this research using qualitative research. The results of this study are factors that influence the formation of morals for every human being, namely: instinctive factors and hereditary characteristics (Al Waritoh). In the implementation of moral education, it is necessary to have the right method for carrying out learning, including; The dialogue method (hiwari), the lecture method, the discussion method, the exemplary method (Al-uswah Hasanah), the story method, the punishment method, the reward method, the habituation method, the repetition method and the parable method. One of the objectives of the Islamic treatise is to perfect the nobility of morality